1974
DOI: 10.1136/jcp.27.4.297
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between urinary infection, cystoscopic appearance, and pathology of the bladder in man

Abstract: PATIENTSFifty bladder biopsies were taken, after full explanation and discussion, from 37 female and four male patients suspected or known to have urinary infections. Thirty-one patients had recurrent cystitis, five painless frequency, and one abdominal pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

1974
1974
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 21 publications
(21 reference statements)
0
10
0
Order By: Relevance
“…We have previously demonstrated a strong correlation between the degree of subepithelial lymphocytic infiltration in the bladder and the occurrence of urinary infection (Marsh et al, 1974). The apparent lack of correlation between infection and squamous change was supported by a similar lack of correlation between squamous change and the subepithelial lymphocytic grading (table III); this was so whether all subjects or only females were considered and was irrespective of the site of biopsy.…”
Section: Squamous Change and Site Of Biopsymentioning
confidence: 68%
See 2 more Smart Citations
“…We have previously demonstrated a strong correlation between the degree of subepithelial lymphocytic infiltration in the bladder and the occurrence of urinary infection (Marsh et al, 1974). The apparent lack of correlation between infection and squamous change was supported by a similar lack of correlation between squamous change and the subepithelial lymphocytic grading (table III); this was so whether all subjects or only females were considered and was irrespective of the site of biopsy.…”
Section: Squamous Change and Site Of Biopsymentioning
confidence: 68%
“…The finding of squamous change was compared with symptoms present in patients at the time of biopsy, and the frequency of symptoms during the prebiopsy observation period, in the manner previously described (Marsh et al, 1974).…”
Section: Squamous Change and Symptomsmentioning
confidence: 99%
See 1 more Smart Citation
“…Light microscopy appeared to be a poor guide to the presence of infection as only half of the 10 group L3 cases had evidence of present infection (group B3 or currently positive MSU), the other five having had infections within the previous three months. These results can be compared with those reported by Marsh, Banerjee, and Panchamia (1974) who used a different system of histological grading and investigated a larger series of cases. They found that definite focal or diffuse lymphocytic infiltration and germinal follicle formation correlated significantly with infection.…”
Section: Discussionmentioning
confidence: 87%
“…With repeat bouts of UTI and chronicity of the disease, there is formation of lymphoid tissue follicles, particularly in the lamina propria of the trigonal region, identified as cystitis follicularis or follicular cystitis. [1][2][3] Contributing to the development of the entity are pathologic anatomic or physiologic factors, which induce and prolong the UTI, such as bladder outlet obstruction, neurogenic or muscular dysfunction of the bladder or the urethra, or relaxation of the pelvic floor, to mention a few. 4 In childhood chronic UTI, resulting from bladder outlet or urethral obstructive disease, or ureteral reflux, there is frequently associated cystitis follicularis, accompanied in many cases by cystitis cystica.…”
Section: Discussionmentioning
confidence: 99%